Drainage basin and topographic analysis of a tropical landscape: Insights into surface and tectonic processes in northern Borneo. (1st July 2016) - Mathew, Manoj Joseph; Menier, David; Siddiqui, Numair; Ramkumar, Mu.; Santosh, M.; Kumar, Shashi; Hassaan, Muhammad
Highlights: Geomorphic analysis demonstrates anomalies in drainage and topography. Streams and valley morphology exhibit characteristics associated with tectonic deformation. Topographic analysis reveals relic landscapes perched at high elevations. Possible rapid uplift phase after 5 Ma creating young topography and enhanced orographic precipitation. Bornean landscape demonstrates transience in response to changes in boundary conditions in present-day. Abstract: We investigated the recent landscape development of Borneo through geomorphic analysis of two large drainage basins (Rajang and Baram basins). The extraction of morphometric parameters utilizing digital terrain data in a GIS environment, focusing on hydrography (stream length–gradient index, ratio of valley floor width to valley height, and transverse topographic symmetry factor) and topography (local relief and relief anomaly), was carried out in order to elucidate processes governing drainage and landscape evolution. Anomalously high and low values of stream length–gradient indices of main tributary streams associated with faults and multiple knick-points along the channel profiles are linked to deformation events. The development of deeply incised V-shaped valleys show enhanced incision capability of streams in response to steepening of hillslope gradients following tectonic inputs. Deflection of streams and probable dynamic reorganization of the drainage system through stream capture processes as feedbacks to tectonic uplift and orographic effect are observed. Local relief and relief anomaly maps highlight the presence of preserved elevation-accordant relict portions of landscapes characterized by low amplitude relief, nested between ridgelines in regions of complex folding. Our results reveal dynamic geomorphic adjustment of the landscape due to perturbations in tectonic and climatic boundary conditions. The implication is that the landscape of north Borneo experienced a tectonic phase of rapid uplift after 5 Ma and undergoes active folding of the Rajang Group thrust belts in the present-day. Active shortening combined with high rates of denudation in Sarawak, demonstrates transience emphasized by the drainage system attempting to adjust to tectonic and climatic forcing.